Caecal microbiota could effectively increase chicken growth performance by regulating fat metabolism. Issue 3 (15th July 2021) - Zhang, Xiaolong; Hu, Yafang; Ansari, Abdur Rahman; Akhtar, Muhammad; Chen, Yan; Cheng, Ranran; Cui, Lei; Nafady, Abdallah A.; Elokil, Abdelmotaleb A.; Abdel‐Kafy, El‐Sayed M.; Liu, Huazhen
Summary: It has been established that gut microbiota influences chicken growth performance and fat metabolism. However, whether gut microbiota affects chicken growth performance by regulating fat metabolism remains unclear. Therefore, seven‐week‐old chickens with high or low body weight were used in the present study. There were significant differences in body weight, breast and leg muscle indices, and cross‐sectional area of muscle cells, suggesting different growth performance. The relative abundance of gut microbiota in the caecal contents at the genus level was compared by 16S rRNA gene sequencing. The results of LEfSe indicated that high body weight chickens contained Microbacterium and Sphingomonas more abundantly ( P  < 0.05). In contrast, low body weight chickens contained Slackia more abundantly ( P  < 0.05). The results of H & E, qPCR, IHC, WB and blood analysis suggested significantly different fat metabolism level in serum, liver, abdominal adipose, breast and leg muscles between high and low body weight chickens. Spearman correlation analysis revealed that fat metabolism positively correlated with the relative abundance of Microbacterium and Sphingomonas while negatively correlated with the abundance of Slackia . Furthermore, faecal microbiota transplantation was performed, which verified that transferring faecal microbiota from adult chickens with high body weight into one‐day‐old chickens improved growth performance and fat metabolism in liver by remodelling the gut microbiota. Overall, these results suggested that gut microbiota could affect chicken growth performance by regulating fat metabolism. Abstract : 16S rRNA gene sequencing indicated that high body weight chickens contained Microbacterium and Sphingomonas more abundantly ( P  < 0.05). In contrast, low body weight chickens contained Slackia more abundantly ( P  < 0.05). The fat metabolism level in liver between high and low body weight chickens was significantly different. Transferring faecal microbiota from adult chickens with high body weight into one‐day‐old chickens improved growth performance and fat metabolism in liver by remodeling the gut microbiota.